KARAKTERISTIK NILAI GIZI DAN ORGANOLEPTIK CUP CAKE DARI BERBAGAI FORMULASI TEPUNG KOMPOSIT: STUDI KEPUSTAKAAN - Ridho Dwi Aminah Tata; Sri Wahyuni; Ansarullah Ansarullah (Jurnal Sains dan Teknologi Pangan, 2023)
ABSTRACT This review aimed to look at the nutritional value and organoleptic characteristics of cupcakes made from various formulations of local food composite flours. Composite flour is flour derived from tubers and cereals with or without wheat or flour and is used as a raw material for processed food. The process of various composite flour formulations was carried out to improve the characteristics of the resulting cupcakes. The results show that the nutritional value of each product formulation was different, and food products made from various composite flour formulations met the Indonesian National Standard (SNI). The results show that the formulation of purple sweet potato flour: flour had the highest nutritional value for water content (35.92%), the formulation of corn flour: spinach flour had the highest protein content (10.05%), the formulation of purple sweet potato flour: flour (23.64%) had the highest fat content, the formulation of corn flour: spinach flour had the highest fiber content (9.16%), and the formulation of black glutinous rice: corn flour had the highest carbohydrate content (62.57%). Meanwhile, the formulation of purple sweet potato flour: flour had the highest organoleptic value for color (3.90), the formulation of black glutinous rice flour: corn flour had the highest organoleptic value for aroma (4.02), the formulation of purple sweet potato flour: flour had the highest organoleptic value for texture (4.19), and the formulation of black glutinous rice flour: corn flour had the highest organoleptic value for taste (4.24). Keywords: cupcakes, nutritional value, composite flour. ABSTRAK Review ini bertujuan untuk melihat karakteristik nilai gizi dan organoleptik cup cake formulasi berbagai jenis tepung komposit pangan lokal. Tepung komposit adalah tepung yang berasal dari umbi-umbian dan serealia dengan atau tanpa tepung terigu atau gandum dan digunakan sebagai bahan baku olahan pangan. Proses formulasi berbagai tepung komposit dilakukan untuk memperbaiki karakteristik cup cake yang dihasilkan. Hasil review menunjukkan bahwa nilai gizi setiap formulasi produk memiliki perbedaan, dan produk pangan yang dihasilkan dari formulasi berbagai tepung komposit dapat memenuhi Standar Nasional Indonesia (SNI). Hasil review menunjukkan bahwa nilai gizi tertinggi untuk kadar air adalah formulasi tepung ubi jalar ungu : tepung terigu sebesar 35,92%, kadar protein tertinggi yaitu formulasi tepung jagung : tepung bayam sebesar 10,05%, kadar lemak tertinggi yaitu formulasi tepung ubi jalar ungu : tepung terigu sebesar 23,64%, kadar serat tertinggi yaitu formulasi tepung jagung : tepung bayam sebesar 9,16% dan kadar karbohidrat tertinggi yaitu formulasi beras ketan hitam : tepung jagung sebesar 62, 57. Nilai organoleptik tertinggi untuk warna adalah formulasi tepung ubi jalar ungu : tepung terigu sebesar 3,90%, nilai aroma tertinggi yaitu formulasi tepung beras ketan hitam : tepung jagung sebesar 4,02%, nilai tekstur tertinggi yaitu tepung ubi jalar ungu : tepung terigu sebesar 4,19%, dan nilai rasa tertinggi yaitu formulasi tepung beras ketan hitam : tepung jagung sebesar 4,24%. Kata Kunci: cup cake, nilai gizi, tepung komposit.